Anion-Accelerated Aromatic Oxy-Cope Rearrangement in Geranylation/Nerylation of Xanthone: Stereochemical Insights and Synthesis of Fuscaxanthone F - Fujimoto, Yuuki; Takahashi, Kanae; Kobayashi, Ryouma; Fukaya, Haruhiko; Yanai, Hikaru; Matsumoto, Takashi (Synlett, 2020)
An efficient installation of a 3,7-dimethylocta-2,6-dien-1-yl (geranyl or neryl) side chain at the C(1) position of a xanthone core by utilizing an anion-accelerated aromatic oxy-Cope rearrangement is described. Experiments revealed that this uncommon rearrangement takes place in a stereospecific manner through a chair-like transition-state structure. An application to the syntheses of the natural xanthone fuscaxanthone F, possessing a geranyl side chain, and its neryl analogue is also described.
Keywords: natural product synthesis; xanthones; oxy-Cope rearrangement; isoprenoids; geranylation; nerylation